Diversidad y abundancia de lepidópteros en cultivos de kiwi del sudeste bonaerense - Alonso, Mariangeles; Divita, Ignacio Federico; Lozano Miglioli, Jorge Raúl; David, Maria Angela; Mondino, Eduardo Ariel; Yommi, Alejandra Karina (Asociación Argentina de Ecología, 2024)
Poster